'The Basilica after the Primitive Christians': Liturgy, Architecture and Anglican Identity in the Building of the Fifty New Churches. Issue 1 (11th May 2016) - Moody, Christopher
Abstract: The London churches built by Nicholas Hawksmoor – the architect required by the Commission for the Fifty New Churches to provide a template for the new churches according to the principles laid down in 1712 – are often regarded as the idiosyncratic creations of the architect's individual genius. They were, however, as much the creation of the particular intellectual, theological and political context of the late Stuart period, an expression of a high church attempt to reconnect the Church of England with the early centuries of the Christian Church, particularly the great basilicas built under Constantine and Justinian. Conservative in intent, they were at the same time fed by the new spirit of intellectual enquiry led by the Royal Society and the expansion of global trade at the start of the eighteenth century. These express a new Anglican denominational identity as the inheritor of the 'purest' traditions of the 'primitive' church, ancient yet modern, orthodox and, at the same time, reformed: one that still influences discussion across the Communion today.